Biochemical Characterization of Ethiopian Black Cumin (Nigella sativa L.) - Basazinew Degu Gebremedin; Bizuayehu Tesfaye Asfaw; Wendawek Abebe Mengesha; Kebebew Assefa Abebe (International Journal of Food Science)
Black cumin (Nigella sativa L.) seed oil has been used for its medicinal and aromatic values. Some studies revealed the presence of variability among N. sativa genotypes in seed oil content and yield. In Ethiopia, very few studies were conducted to investigate the variability of N. sativa genotypes by using biochemical traits. Thus, this study was conducted at Debre Zeit and Kulumsa Agricultural Research Centers’ experimental sites under field conditions during the 2021 cropping season to investigate the variability of Ethiopian N. sativa genotypes based on biochemical traits. Sixty-four genotypes were used and arranged in an 8×8 simple lattice design with two replications. Essential oils (EOs) and fixed oils were extracted by the respective methods of hydro distillation and solvent extraction. The univariate, bivariate, and multivariate analyses of the collected data were performed. Combined analysis of variance (ANOVA) revealed significant differences among genotypes in fixed oil yield per hectare (FOY), EO content (EOC), and EO yield per hectare (EOY). EOY had a significant positive correlation with FOY and EOC. It is expected to improve all biochemical traits by 17.39%–94.62% over the improved varieties by selection of the top 5% landraces. Therefore, genotypes 90504, 219970, and 013_ATH were the top 5% best performed landraces by FOY and EOY over the improved varieties. So, through selection, it would also be possible to improve the studied biochemical traits of the genotypes. The principal component (PC) analysis (PCA) of four biochemical traits showed 85.86% of the total variance captured by the first two PCs. EOY and FOY were the main contributor traits to the variation in the first PC, whereas FOC and EOC were the main contributor traits to the variation in the second PC. The genotypes were grouped into three different clusters based on four biochemical traits with significant intercluster distance. This showed that there was sufficient diversity among the genotypes which can be exploited for the future N. sativa improvement program in Ethiopia.